PENGARUH PENAMBAHAN TEPUNG TAPIOKA PADA PEMBUATAN BISKUIT BEBAS GLUTEN, BEBAS KASEIN BERBAHAN BAKU TEPUNG UBI JALAR UNGU (Ipomoae batatas L ). - Penina P. Hindom; Lucia C. Mandey; Erny Nurali (Universitas Sam Ratulangi, 2016)
ABSTRACTThis study aims to determine the amount of the addition of tapioca flour right in making biscuits purple sweet potato (ipomoea batatas L). Analyze the nutritional content of gluten and casein-free biscuits are produced. Evaluate the sensory quality of the biscuits are produced. This study uses a completely randomized design with mixing treatment with a purple sweet potato starch and tapioca starch. Each - each 4 treatments performed 3 repetitions. Treatment A (10% addition of tapioca starch), B (15% addition of tapioca starch), C (20% addition of tapioca starch), D (25% addition of starch). Variables were observed in this study is the chemical content of the biscuit the water content, ash content, protein content, fat, crude fiber, carbohydrate, calorie value. Based on test results obtained organoleptic formula mixture of sweet potato flour and tapioca flour are the preferred panelists namely D (Extra 25% starch) and has the chemical content of water content (3,25%), ash content (2,80%), fat ( 22,74%), crude fiber (0,76%), protein (2,91%), carbohydrates (68,28%), a calorofic value (490,11 kcal). Keywords : Purple Sweet Potato Starch, Tapioca Starch, Confectionery.